Retrograde Intrarenal Surgery Following Laser Endopyelotomy; Sequential Procedures for Ureteropelvic Junction Obstruction and Nephrolithiasis - Kartal, Ibrahim; Tuygun, Can; Karakoyunlu, Ahmet Nihat; Sandikci, Fatih; Baylan, Burhan; Ersoy, Hamit (Urology Journal, 2019)
Purpose: This study was designed to evaluate the effectiveness and safety of retrograde intrarenal surgery (RIRS) following retrograde laser endopyelotomy (rLEP) in concomitant ureteropelvic junction obstruction (UPJO) and stone disease. Materials and Methods: Patients with concomitant UPJO and renal stone disease who were first treated in our clinic by rLEP for obstruction and then RIRS for stone disease were enrolled. Study period went from 2012 to 2017. RIRS following rLEP was performed earliest at the sixth week. Patients who underwent rLEP were matched with those with normal anatomy at a 1:1 ratio based on the propensity scores. Additionally, clinical results were compared in order to evaluate the effects of rLEP surgery on RIRS. Subsequently, patients who underwent RIRS following rLEP were independently evaluated and factors affecting the success of sequential procedures were investigated. Results: The sole difference between those that underwent RIRS following rLEP (n=27) and controls with normal anatomy that underwent RIRS was in operative times (p = .011). Evaluation of potential success factors in the sequential rLEP-RIRS group revealed that primary etiology, obstruction length less than 1cm, smaller stone size and presence of single stone showed significant effects (p = .047, p = .030, p = .040, p ? .001, respectively). RIRS following rLEP generated an 81.5% stone-free and, after a median follow-up time of 32 months, a 74.1% obstruction-free rate. Conclusion: RIRS following rLEP in patients with UPJO and renal stones is an effective treatment method. It can be used safely in patients with single stones < 2cm, short obstruction lengths, and presence of primary etiology.